May Measurement Month 2017: an analysis of blood pressure screening results in Austria—Europe. (24th April 2019) - Perl, Sabine; Zweiker, David; Niederl, Ella; Kolesnik, Ewald; Zweiker, Gudrun; Kraler, Elisabeth; Stoff, Ingrid; Haberfeld, Heinz; Dichtl, Wolfgang; Koppelstätter, Christian; Lhotta, Karl; Ederer, Herbert; et al.
Abstract: Elevated blood pressure (BP) is a growing burden worldwide, leading to over 10 million deaths each year. May Measurement Month (MMM) is a global initiative aimed at raising awareness of high BP and to act as a temporary solution to the lack of screening programs worldwide. An opportunistic cross-sectional survey of volunteers aged ≥18 was carried out in May 2017. Blood pressure measurement, the definition of hypertension (HTN), and statistical analysis followed the standard MMM protocol. In total, 2711 individuals (58.6% female) were screened during MMM17 in 56 centres. After multiple imputation, 1704 (62.9%) had HTN (≥140/90 mmHg). Of individuals not receiving antihypertensive medication, 764 (43.2%) were hypertensive. Of individuals receiving antihypertensive medication, 597 (63.5%) had uncontrolled BP. MMM17 was one of the largest BP screening campaigns undertaken in Austria. A large number of undiagnosed hypertensives was found and connected to a therapeutic strategy. An alarming number of uncontrolled but treated hypertensives should attract the attention of doctors and health care system in Austria.